Pengaruh Terapi Slow Stroke Back Massage (SSBM) terhadap Penurunan Tekanan Darah pada Pasien Hipertensi RSKD Dadi - Nur Havid Reynaldi; Makkasau Plasay; Muh Yusuf Tahir (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Hypertension is a chronic health problem whose prevalence continues to increase and is a major risk factor for cardiovascular disease. In addition to pharmacological therapy, non-pharmacological interventions are needed to help control blood pressure safely and sustainably. One complementary therapy that has the potential to lower blood pressure is Slow Stroke Back Massage (SSBM), which works through relaxation mechanisms and modulation of the autonomic nervous system. This study aims to determine the effect of SSBM therapy on reducing blood pressure in hypertensive patients in the Camar Room of RSKD Dadi, South Sulawesi Province. The study used a quantitative quasi-experimental design with a two-group pretest–posttest design. A sample of 32 respondents was selected using a purposive sampling technique, divided into an intervention group and a control group. Data collection was carried out by measuring systolic and diastolic blood pressure before and after the intervention using a standard sphygmomanometer. The results showed a significant decrease in systolic and diastolic blood pressure in the group receiving SSBM therapy compared to the control group. Thus, SSBM therapy has a significant effect on reducing blood pressure in hypertensive patients and can be recommended as a complementary therapy in nursing care.